2023
DOI: 10.1111/eci.14072
|View full text |Cite
|
Sign up to set email alerts
|

Washed microbiota transplantation improves haemoglobin levels in anaemia of chronic disease

Abstract: BackgroundAnaemia of chronic disease (ACD) is the second most common type of anaemia and lacks an effective treatment. Patients with anaemia are reported to have altered gut microbial profiles, which may affect erythropoiesis. Here, we investigated the gut microbial features of patients with ACD and determined whether regulating gut microbiota using washed microbiota transplantation (WMT) was effective in treating ACD.MethodsWe compared the gut microbiota profile of patients with ACD and healthy controls, eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Healthy donor screening, washed microbiota suspension preparation, and microbiota transplantation were conducted following previously established protocols. 48 A questionnaire assessing medical history, fecal examination for pathogens, and blood tests was used to screen potential donors. The bacterial suspension was prepared in a Biosafety Level 2 laboratory with the assistance of skilled professionals who exclusively used disposable sterile materials.…”
Section: Methodsmentioning
confidence: 99%
“…Healthy donor screening, washed microbiota suspension preparation, and microbiota transplantation were conducted following previously established protocols. 48 A questionnaire assessing medical history, fecal examination for pathogens, and blood tests was used to screen potential donors. The bacterial suspension was prepared in a Biosafety Level 2 laboratory with the assistance of skilled professionals who exclusively used disposable sterile materials.…”
Section: Methodsmentioning
confidence: 99%
“… 48 Another study showed that the α-diversity of gut microbiota in patients with chronic disease is significantly lower than that in healthy controls, which is accompanied by the decreased abundances of Faecalibacterium , Lachnoclostridium , Lachnospiraceae NK4A136 group, and Butyricicoccus genera. 49 Soriano-Lerma et al 50 demonstrated that iron-deficiency anemia results in intestinal dysbiosis manifested as an increase in SCFA-producing bacteria and SCFA concentration in the colon of rat model. This could be a trade-off mechanism against disease, indicating that supplementation of SCFA or SCFA-producing bacteria may be beneficial to iron-deficiency anemia patients.…”
Section: Gut Microbiota and Nonmalignant Hematological Diseasesmentioning
confidence: 99%